Comparison between POES energetic electron precipitation observations and riometer absorptions: Implications for determining true precipitation fluxes. Issue 12 (3rd December 2013) - Rodger, Craig J.; Kavanagh, Andrew J.; Clilverd, Mark A.; Marple, Steve R.
Abstract [1] Energetic electron precipitation (EEP) impacts the chemistry of the middle atmosphere with growing evidence of coupling to surface temperatures at high latitudes. To better understand this link, it is essential to have realistic observations to properly characterize precipitation and which can be incorporated into chemistry‐climate models. The Polar‐orbiting Operational Environmental Satellite (POES) detectors measure precipitating particles but only integral fluxes and only in a fraction of the bounce loss cone. Ground‐based riometers respond to precipitation from the whole bounce loss cone; they measure the cosmic radio noise absorption (CNA), a qualitative proxy with scant direct information on the energy flux of EEP. POES observations should have a direct relationship with ΔCNA and comparing the two will clarify their utility in studies of atmospheric change. We determined ionospheric changes produced by the EEP measured by the POES spacecraft in 250 overpasses of an imaging riometer in northern Finland. The ΔCNA modeled from the POES data is 10–15 times less than the observed ΔCNA when the >30 keV flux is reported as <106 cm−2 s−1 sr−1. Above this level, there is relatively good agreement between the space‐based and ground‐based measurements. The discrepancy occurs mostly during periods of low geomagnetic activity, and we contend that weak diffusion is dominating the pitch angle scattering into the bounce loss cone at these times. A correction to the calculation using measurements of the trapped flux considerably reduces the discrepancy and provides further support to our hypothesis that weak diffusion leads to underestimates of the EEP.